Energy-based critical plane fatigue methods applied to additively manufactured 18Ni300 steel - Cruces, A.S.; Branco, Ricardo; Borrego, L.P.; López-Crespo, Pablo (Elsevier, 2023)
In this work, the uniaxial and biaxial fatigue behaviour of maraging steel (18Ni300) obtained by additive manufacturing was studied. The material was evaluated using several biaxial load paths and different load levels. The predictive capacity of the fatigue life and crack initiation angle of the critical plane methods of Liu (I and II), and Chu, Conle, and Bonnen (CCB) were evaluated. The results obtained showed that normal stresses had a strong effect on the fatigue life. In general, the best estimates of the useful life and initial crack angle prediction were obtained with the CCB method.
Keywords: Metales -- Fatiga; Fatiga (Fisiología); Biaxial fatigue; Mean stress; 18Ni300 maraging steel; 18Ni300 AM; Critical plane methods